PERAN MODEL PEMBELAJARAN PJOK DALAM MENINGKATKAN MOTIVASI DAN PARTISIPASI BELAJAR SISWA DI SEKOLAH DASAR - Ely Yuliawan; Putri Ihratun; Winda Ariyani; M. Adrion Nugraha; Johan Agus Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physical Education, Sports, and Health (PJOK) learning in elementary schools requires appropriate learning models to optimally improve students’ learning outcomes. This study aims to examine the role of PJOK learning models in improving elementary school students’ learning outcomes through a literature review. The research method used was a literature study by analyzing ten national journal articles published between 2022 and 2025. The data were analyzed using a descriptive qualitative approach by reviewing research findings related to the implementation of various PJOK learning models. The results indicate that cooperative learning, Teaching Games for Understanding (TGfU), Problem Based Learning, discovery learning, game-based learning, blended learning, and differentiated learning models have a positive effect on improving students’ cognitive, affective, and psychomotor learning outcomes. Student-centered learning models are proven to be more effective than conventional learning approaches. Therefore, the implementation of varied and innovative PJOK learning models is essential to enhance the quality of learning and learning outcomes in elementary schools.